Stoichiometry unbalance and photoluminescence emission in Ga1-XAsX films prepared by flash evaporation - da Silva, JHD; Leite, DMG; Martins, M. R. (Elsevier B.V., 2004)
Both narrow and broad photoluminescence bands were observed in Ga1-XAsX films prepared by flash evaporation of polycrystalline GaAs containing native C impurities. The observed narrow crystalline-like bands are similar to band-to-band and C acceptor impurity emissions in crystalline GaAs. The narrow bands are evidence that the As excess favors the PL active GaAs crystallite formation in films deposited onto silicon (10 0) substrate, even when the As excess is very large (X = 0.84). This favoring is not observed in twin samples grown on silica glass substrates nor on Ga rich samples, indicating the important role of the combined effect of the As excess and Si substrate in the GaAs crystallite formation. The broad amorphous-like bands were observed in Ga rich and in moderately As rich samples. The photoluminescence emission is compared with the microstructure of the material as determined from the micro-Raman, absorption edge and reflectance measurements. The volume fraction of the crystallites formed is small and PL emission indicates that the crystallite electronic quality is much better than the ones formed heat treating films grown on silica glass substrates. (C) 2004 Elsevier B.V. All rights reserved.